Caregiver–Child Discrepancies in Reports of Child Emotional Symptoms in Pediatric Chronic Pain. (30th December 2019) - Martin, Sarah R; Zeltzer, Lonnie K; Seidman, Laura C; Allyn, Katherine E; Payne, Laura A
Abstract: Objective: Pediatric chronic pain evaluation includes self-reports and/or caregiver proxy-reports across biopsychosocial domains. Limited data exist on the effects of caregiver–child discrepancies in pediatric pain assessment. In children with chronic pain, we examined associations among discrepancies in caregiver–child reports of child anxiety and depressive symptoms and child functional impairment. Methods: Participants were 202 children ( M age =14.49 ± 2.38 years; 68.8% female) with chronic pain and their caregivers (95.5% female). Children and caregivers completed the Revised Child Anxiety and Depression Scale (RCADS) and RCADS-Parent, respectively. Children also completed the Functional Disability Inventory. Mean difference tests examined caregiver–child discrepancies. Moderation analyses examined whether associations between child self-reported anxiety and depressive symptoms and functional impairment varied as a function of caregiver proxy-report. Results: Children reported more anxiety and depressive symptoms compared with their caregivers' proxy-reports ( Z = −4.83, p < .001). Both informants' reports of child anxiety and depressive symptoms were associated with child functional impairment ( r s = .44, r s = .30, p < .001). Caregiver proxy-report moderated associations between child-reported anxiety and depressive symptoms and functional impairment ( B = −0.007, p = .003). When caregiver proxy-report was low, child self-reported anxiety and depressive symptoms were positively related to functional impairment ( B = 0.28, SE = 0.07, 95% CI [0.15, 0.41], p < .001). Conclusions: Discrepant caregiver–child perceptions of child anxiety and depressive symptoms may be associated with functioning in children with chronic pain, especially when caregivers report less child internalizing symptoms. These findings highlight the need for further examination of the effects of caregiver–child discrepancies on pediatric chronic pain outcomes and may indicate targets for intervention.